Miss Alice Paul on Hunger Strike (1917) - Anonymous (Clinical Sociology Review)
WASHINGTON. Nov. 6 – Alice Paul, National Chairman of the Woman’s Party, now doing a seven months’ sentence in jail here for picketing the White House, has gone on a hunger strike, and tonight she had been in the jail hospital without food for the preceding twenty- four hours, stolidly threatening to starve herself to death unless her six companions, serving time for the same offence, got better food.